Pollution Characteristics of Sb, As, Hg, Pb, Cd, and Zn in Soils from Different Zones of Xikuangshan Antimony Mine - Saijun Zhou; Andrew Hursthouse; Tengshu Chen (Journal of Analytical Methods in Chemistry)
Major sources of pollution during the antimony (Sb) mining and processing are mining waste rock, smelting waste, tailings dam, and underground tunnel wastewater. The aim of the present study was to assess magnitude of pollution from Sb mine by taking four types of samples: soil in the mining waste rock zone, soil in the smelting zone, soil in tailings zone, and soil in underground tunnel wastewater zone. Sixty soil samples from the four zones were taken for experimental work, and the contents and morphological characteristics of the six potentially toxic elements (PTEs) such as Sb, As, Hg, Pb, Cd, and Zn in the soil samples were measured by using a hydride generation atomic fluorescence spectrometer (AFS-9700). The results show that the soil of the mine area is seriously polluted. The average contents of Sb, As, Hg, Pb, Cd, and Zn in the soil reach 1267.20 mg·kg−1, 94.44 mg·kg−1, 1.46 mg·kg−1, 184.19 mg·kg−1, 8.54 mg·kg−1, and 1054.11 mg·kg−1, respectively. There exists good correlation between the PTEs in the soil, with Sb strongly positively correlated with As, Hg, Pb, and Zn. The intensity of pollution is highest in the antimony-smelting zone, where the potential ecological risk index is over 15,000, followed by the tailings zone and mining waste rock zone, with the underground tunnel wastewater zone being the lowest. Using sequential chemical extraction, the elements are associated with the residual fraction, followed by organic-sulfide fraction, and smaller portions in the Fe-Mn oxide, carbonate, and exchangeable fractions. There are great differences in the speciation content of different elements in different sampling zones. The study implicates that Sb-smelting zone is the potential source of PTEs and maximum metals are associated with residual phase, out of which significant portion is associated with mobile fraction or phase.